CORRELATION OF GLOBAL LONGITUDINAL SYSTOLIC STRAIN WITH SEVERITY OF CORONARY ARTERY DISEASE IN NON-ST-ELEVATION ACUTE CORONARY SYNDROME HAVING NORMAL EJECTION FRACTION - Muhammad Khaleel Iqbal,; Muhammad Saleem Awan,; Usman Mahmood Butt,; Shahzad Tawwab,; Muhammad Furrakh Maqbool, (Journal of Ayub Medical College Abbottabad, 2021)
Background: In patients of non-ST-elevation acute coronary syndrome (NSTEACS), the global longitudinal peak systolic strain (GLPS) has been used to detect the presence of coronary artery disease (CAD) before left ventricular ejection fraction (LVEF) is affected. We tried to find out the correlation between the GLPS and severity of CAD in such patients. Methods: A descriptive correlational study was conducted from March 2018 to January 2020 at Jinnah Hospital Lahore. Two hundred and sixteen patients of NSTEACS with EF of ‰¥60% were included. Patients were divided according to angiographic results into those having non-significant, one-vessel, two-vessel or three-vessel disease. These four groups were compared regarding left ventricular end-systolic dimension (LVESD), left ventricular end-diastolic dimension (LVEDD), LVEF, global longitudinal peak systolic strains in apical long axis view (GLPS-APLEX), in apical 4-chamber view (GLPS-A4C), in apical 2-chamber view (GLPS-A2C) and average of these (GLPS-AVG). All these parameters were also compared between patients having and those not having left main coronary artery (LMCA) disease. Results: Out of 216 patients, males and females were 124(57.4%) and 92 (42.6%) respectively. There were 28 (13.0%), 83 (38.4%), 62 (28.7%) and 43 (19.9%) patients who had non-significant, one-vessel, two-vessel and three-vessel CAD respectively. With increase in severity of CAD, GLPS-AVG progressively decreased from non-significant CAD being 20.6±0.7 to three-vessel CAD being 16.1±0.7. There was a significant negative correlation between severity of CAD and all of the GLPS-APLEX, GLPS-A4C, GLPS-A2C and GLPS-AVG (p<0.001 in all). GLPS-AVG was significantly low in patients having LMCA disease (16.5±0.7) than those not having LMCA disease (18.2±1.5) with p-value of <0.001. All other types of GLPSs showed the similar trend. Conclusion: Global longitudinal peak systolic strain has a significant negative correlation with severity of coronary artery disease in non-ST-elevation acute coronary syndrome having normal ejection fraction.